Symbols, Speech, and Electoral Influence: An Educational Sociolinguistic Study of Political Jargon in the 2024 Election - Aprilia, Fitria; Neisya; Azzahra, Siti Fatimah (Universitas Jambi, Indonesia, 2024)
This study employs a qualitative and descriptive library research method to analyse viral political jargon circulating on social media, such as